Helminths of Lizards (Reptilia: Squamata) from Mato Grosso State, Brazil - Avila, Robson W. [UNESP]; Da Silva, Reinaldo J. [UNESP] (Helminthological Soc Washington, 2011)
Fifty-five specimens from 11 lizard species (Ameiva ameiva, Bachia scolecoides, Cercosaura ocellata, Hemidactylus mabouia, Hoplocercus spinosus, Iguana iguana, Mabuya nigropunctata, Plica umbra, Tropidurus torquatus, Tupinambis merianae, and Tupinambis teguixin), collected in 3 ecosystems (Amazon, Cerrado, and Pantanal) from the state of Mato Grosso in midwestern Brazil, were examined for endoparasites. Sixteen nematode species (Alaeuris vogelsangi, Cruzia travassosi, Diaphanocephalus galeatus, Oswaldocruzia sp., Oswaldocruzia vitti, Oswaldofilaria sp., Ozolaimus megatyphlon, Parapharyngodon sceleratus, Physaloptera hatzi, Physaloptera retusa, Physaloptera sp., Pica tuba digiticauda, Rhabdias sp., Skrjabinodon heliocostai Spinicauda spinicauda, and Strongyluris oscari), 2 cestode species (Oochoristica travassosi and Oochoristica vanzolinii), and 2 trematode species (Helicotrema sp. and Paradistomum parvissimum) were recovered. Eleven new host records and 10 new state (I new country) records were reported.
Keywords: parasites; Nematoda; Sauria; Neotropical; South America